STRATEGI DAKWAH MAJELIS TAKLIM NGAJI NGOPI DARBY DALAM MENINGKATKAN PEMAHAMAN ILMU AGAMA DI DUSUN SRONO - PUTRA, RIDHO PRATAMA; HADIONO, ABDI FAUJI (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research explores the da'wah strategy implemented by theNgaji Ngopi Darby Taklim Council in Srono Hamlet, Banyuwangi,to increase understanding of religious knowledge in thecommunity. Founded in 2011 by KH. Abdul Basyhir, this assemblyaims to strengthen faith and religious knowledge through regularweekly recitations. Using a qualitative approach with descriptivemethods, this research collects data through observation,interviews and documentation. The research results show that thisassembly uses sentimental and rational preaching strategies, as wellas lecture and question and answer methods using Sufism material.This strategy is designed to change people's attitudes, increase thespirit of worship, and strengthen ties between Muslims. Thisresearch makes an important contribution to the development ofunderstanding of religion in society and highlights the role of the57taklim assembly as a non-formal educational institution that isadaptive and effective in conveying Islamic teachings.